Improving the effectiveness of English as a medium of instruction in sub-Saharan Africa - Clegg, John; Simpson, John (Comparative education, 2016)
Most academic discussion on the role of language in education in sub-Saharan Africa (SSA) supports the extended use of African languages as media of instruction (MoI), while most practice preserves a monolingual role for European languages. Many ministries of education maintain the belief that African languages are not appropriate as MoIs beyond the early years. In African countries in which English is the MoI, many learners in primary school and beyond do not have sufficient ability in English to achieve grade-appropriate subject knowledge. This restricts their access to effective classroom practice and thus to the curriculum. Pedagogical and organisational expertise appropriate to education for learners working in a second language is available both in Africa and other parts of the world, but rarely widely applied in SSA. This article describes relevant educational practices which are successfully used in these different contexts and which could be extended in SSA. They include ways of easing the transition from early years education in an African language, multilingual classroom practice, the pedagogy of language-supportive subject teaching, accessible textbook design, appropriate curriculum for learners working in a second language, language-appropriate assessment and the management of multilingual education.